Tuning electrical conductivity in AlN-based ceramics by incorporating graphene. Issue 5 (May 2023) - Kenfaui, Driss; Guillemet-Fritsch, Sophie; Valdez-Nava, Zarel; Laudebat, Lionel; Tenailleau, Christophe; Dufour, Pascal; Locatelli, Marie-Laure
Abstract: Aluminum nitride (AlN) is the material of choice for high power modulus substrates. The thermal and electrical conductions can be also fostered by adding CaF2 and carbon particles, respectively. Moreover, additives (Y2 O3 ) have to be used as sintering aids to achieve full densification. In this paper, we report on tuning the electrical conduction within AlN-based composites developed by incorporating graphene nanoplatelets GNP, obtained from graphite exfoliation, in the AlN-based ceramics comprising Y2 O3 and CaF2 . These composites were prepared by Spark Plasma Sintering through a new configuration called "multiple preparation" with a view to fabricating three samples per cycle, revealing time and energy savings. An increase of the electrical conductivity by 10 orders of magnitude was obtained for these composites compared to the commercial AlN by adjusting the amount of GNP and the way of exfoliation. This work promotes the development of novel multifunctional ceramic composites for Power Electronics applications.